The Effectiveness of News Broadcasting Via 98.7 Fm Radio Among UI Vocational Students in The Media Production Study Program - Iwan Iraka; Wahyunengsih Wahyunengsih (Jurnal Pengetahuan dan Pendidikan, 2023)
This study discusses the effectiveness of news broadcasting through 98.7 Fm Radio among UI vocational students in the Media production Study Program. This study has a formulation of the problem with the formulation of the problem as follows, how effective is the news broadcast on radio 98.7 fm among students UI media production Studies program. The purpose of this study was to determine the extent and whether it is effective news broadcast on radio 98.7 fm. This study uses descriptive quantitative methods, this method aims to create an image or descriptive of a situation objectively using numbers, starting from data collection. The Data was obtained through questionnaires distributed to respondents, namely UI vocational students with Media Production study programs with a predetermined number of respondents, namely as many as 35 respondents. The results were analyzed using statistical analysis of descriptive data. The results of this study showed that penyampain broadcast news via Radio 98.7 fm is already quite effective, evidenced by the answers of respondents who answered agree and strongly agree in the range of 70-90% answered effectively, which starts from the way the news carried by broadcasters are fast but also clear details, according to existing facts and reliable sources of information will obviously be its validity. In addition, enough information is provided quality, latest, useful and memabntu drivers, especially those who are on the road by listening to the news presented by this 98.7 Fm Radio. However, broadcasting news via radio 98, 7fm and other radio for now has begun to be replaced by other mass media that are more modern and more interesting.